Soekarno’s Idea About Indonesian Revolution In 1945-1957 - Jamil, Robit Nurul; Sumarjono, Sumarjono; Soepeno, Bambang (JURNAL HISTORICA, 2017)
Indonesian revolution is a social change which takes place quickly cover the base or the main points of social life. The study in this context is the study of social change that is experienced by people in the review of social history and intellectual history in order to focus on the historical actor as the main study. The goal of a study is to examine the idea of Soekarno about Indonesian revolution in 1945-1967. Besides, the benefit of the study is a workout of writing a scientific work. This study also applies the method of historical research which its steps are heuristic, criticism, interpretation, and historiography. Moreover, the theory used in a study is the Marxian conflict theory. Meanwhile, the approach applied in a study is the sociology of knowledge and anthropology. The result obtained in a study is the consistency of Soekarno’s thought toward Indonesian revolution, one goal, one basic, one principle revolution, one principle struggle and many kinds of struggle tactics. The conclusion is the condition of Indonesian people who suffer from difficulty because of the ferocity of Imperialism and Capitalism in Indonesia. The environmental condition around Soekarno influences his mindset. The education condition influence a paradigm and a view to thinking about revolution. Keywords: Soekarno’s idea and Indonesian revolution